Mathematical Beliefs and Practiceso of Trained Graduate Teachers of JNVS of Bihar - Yadav, Rahul Kumar (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Mathematics occupies an essential place in the school curriculum. The present study involved the exploration of mathematics teachers‘ beliefs about teaching and learning of mathematics at the upper primary stage. The participants‘ were ten TGTs of JNVs of Bihar. The open-ended questionnaires, rating scales, and classroom observations were conducted in five JNVs with two female and eight male mathematics teachers. The open-ended questionnaire focussed on the pedagogical beliefs about mathematics and examined whether these beliefs are related to the traditional, process, or constructivist approaches. Classroom observations allowed the researcher to visualize whether mathematics teachers‘ beliefs about teaching and learning implemented in the classroom. The rating scale was analysed to identify and assess common themes among their beliefs as well as associations between their beliefs and classroom practices. The findings revealed that most of the mathematics teachers‘ beliefs about teaching and learning represented the process approach or constructivist approach. The study shows a significant shift toward the process approach in upper primary mathematics education. Pedagogical implications have been suggested by the researchers based on the findings of the study.